Adaptive fault-tolerant sliding mode control for Markovian jump systems via delta operator method. (1st February 2018) - Zhao, Dongyang; Liu, Yu; Liu, Ming; Yu, Jinyong
Abstract: This paper investigates the adaptive fault-tolerant control problem of a class of Markovian jump systems with high frequency sampling. In this design, matched non-linearity, unknown actuator degradation factor and unmeasurable states are considered in a unified framework. First, an adaptive sliding mode observer approach is developed to obtain the estimates of system state vector. Second, based on the state estimation, an integral-type sliding surface for the overall closed-loop delta operator system is presented, and a sliding mode control law is proposed to guarantee the stochastic stability of the fault closed-loop system. Finally, a simulation example is provided to verify the effectiveness of the designed fault-tolerant control method.